Enhanced sensitivity towards LPG with selectivity between LPG, NO2, and NH3 by novel CoFe2O4/SiC/BaTiO3 nanocomposites. Issue 10 (15th May 2023) - Rathore, Rishi Raj Singh; Desarada, Sachin Vijay; Chaure, N.B.; Pandey, R.K.; Rathore, Deepshikha
Abstract: In this paper, the enhanced sensitivity and selectivity between LPG, NO2, and NH3 by novel CoFe2 O4 /SiC/BaTiO3 (CFO/SiC/BTO) ternary nanocomposites synthesized by chemical coprecipitation and solid-state methods have been reported. The structural and morphological properties of nanocomposites were analysed using XRD, SEM and EDS respectively. The highest dielectric permittivity ∼665 at 8 kHz for 30 wt% BTO with lowest dielectric loss at high temperature was achieved using LCR meter. Moreover, the maximum response (%) was obtained towards LPG ∼84%, while it was found to be ∼11% for NH3 and ∼23% for NO2 at 220 ppm, whilst it was achieved more than 95% above 150 °C for all the gases. Furthermore, the selectivity ∼95% at room temperature was acquired for LPG in presence of NH3 . The excellent response (%) ∼ 99.68% and 99.85% was obtained for mixture of LPG-NO2 and LPG-NH3 at 300 °C for 30 wt% BTO, which was also confirmed by obtained activation energy. Accordingly, 30 wt% BTO of CFO/SiC/BTO nanocomposites is providing excellent sensitivity and selectivity towards LPG in the mixture of NO2 and NH3 .